Academic performance and emotions of elementary school students in an intervention with immersive technologies in the mathematics classroom (Innovaciones Educativas, 2025)
Evidence about the effect of immersive technologies on learning is contradictory, because it is often payed more attention to technology than to pedagogy. This research sought to determine the effect of augmented reality and virtual reality in academic performance of Forth grade students in Mathematics, as well to describe the achievement emotions in the pedagogical intervention. The before and after design was developed with a group of 35 students, 21 boys and 14 girls, with 9 years in average, belonging to a school in Chile. The intervention consisted in three 90-minutes sessions where students interacted with technologies to enhance their geometrical concepts. In addition, to assess learning content tests were administrated before and after the intervention, and a questionnaire of emotions during it. Results reveled a significant effect in the academic performance, demonstrating a large effect size (d = .79). Findings indicate absence of significant differences in performance between boys and girls. Furthermore, positive emotions in the activities were identified. Research advocates for prioritization of objectives and learning outcomes above the technological contribution.
Keywords: academic performance; learning; mathematics; technology; basic education